Amyloid beta pathology induces astrocytic pTDP-43 mislocalization and disrupts TDP-43-regulated cryptic exon transcripts. - Rafiee, Zeinab; Santiago, Jessica; Andersson, Emelie; Hansson, Oskar; Wennström, Malin (Frontiers in Aging Neuroscience, 2026)
Background: While amyloid-β (Aβ) and tau are hallmark pathologies of Alzheimer's disease (AD), TDP-43 proteinopathy is increasingly recognized as an important contributor, occurring in up to 57% of AD cases and associated with accelerated cognitive decline. TDP-43 regulates RNA splicing, and its mislocalization leads to cryptic exon inclusion and loss of canonical protein function. While neuronal TDP-43 pathology has been well studied, its role in astrocytes remains less understood. Recent findings suggest increased phosphorylated TDP-43 (pTDP-43) inclusions in astrocytic endfeet in AD and a bidirectional interaction between Aβ and TDP-43, promoting mutual aggregation. Methods: We analyzed pTDP-43 immunoreactivity (IR) in astrocytic perivascular end-feet, nuclei, and cytosol in hippocampal sections from 3-month-old and 18-month-old AppNL–F/NL–F mice and 18-month-old wild-type controls using ImageJ. In vitro , primary fetal human astrocytes were exposed to oligomeric Aβ42, and changes in cytosolic and nuclear pTDP-43 IR were quantified via ImageJ, while TDP-43 and pTDP-43 protein levels were measured using an in-house ELISA. Expression of canonical transcripts ATG4B and KALRN, involved in autophagy and synaptic support, was assessed by qPCR. Corresponding protein-level changes were evaluated using in-house ELISA. Results: Our findings demonstrate significantly higher pTDP-43 accumulations in astrocytic nuclei, cytosol, and endfeet in 18-month-old AppNL–F/NL–F mice compared to age-matched wild-type mice. Astrocytes exposed to oligomeric Aβ42 showed elevated cytosolic pTDP-43 IR and total pTDP-43 protein levels. Concurrently, expression of canonical ATG4B and KALRN transcripts was significantly reduced, which was accompanied by corresponding decreases in protein levels. Conclusion: Our findings demonstrate that pTDP-43 accumulates in astrocytic nuclei, cytosol, and endfeet in the presence of AD pathology. The observed Aβ-induced increase in cytosolic pTDP-43 and transcript disruption suggests a mechanistic link contributing to autophagy impairment and cytoskeletal changes in astrocytes, potentially exacerbating AD progression.